Wörter - Zeichen der Veränderung - Bopp, Dominika; Ptashnyk, Stefaniya; Roth, Kerstin; Theobald, Tina (Studia linguistica Germanica, 2020)
Words are symbols for the things and facts of the world. This volume focuses on the ways that words may be seen as “signs of change” in this world, based on numerous examples. Alongside the history of words and concepts, the essays examine questions of the codification of historical lexicons, the dynamics of professional and political language, and the transformation of communicative practices and traditions of verbal expression.
Keywords: Aufsatzsammlung; Wortschatz; Wortfeld; Wort; Deutsch